Strategi Sekolah dalam Menyesuaikan Kurikulum dengan Kebutuhan dan Karakteristik Siswa di SD 101766 Bandar Setia - Iasyah Fakhrany; Ananda Putri Humairoh; Putri Adhelia Br Damanik; Putri Nurul Auliyah; Nia Diana Situmorang; Yohana Mitra Enjelika Tambunan; Asiah Ramadhani (Universitas Palangka Raya, 2025)
As a strategy implemented by SD 101766 Bandar Setia in adjusting the curriculum to meet the needs and characteristics of diverse students. In the modern era, the curriculum acts as the main guideline in the learning process, and its effectiveness is highly dependent on the ability of educational institutions to adapt to the diversity of learners. Using a qualitative approach, this research relies on in-depth interviews with teachers to identify the various adaptation strategies implemented. Some of these include the implementation of module-based learning models, the utilization of interactive digital technology, and the use of portfolio-based assessment systems. Although there are still challenges, such as limited infrastructure and gaps in teacher competencies, the efforts made reflect a commitment to creating an education system that is more inclusive and adaptive to change.